FX Market Returns and Their Relationship to Investor Fear - Smales, Lee; Kininmonth, J. (Wiley-Blackwell Publishing Asia, 2016)
This note examines the relationship between changes in levels of investor fear (measured by the implied volatility index) and foreign exchange market returns. Our empirical results indicate a negative relationship between daily returns on high-interest rate (investing) currencies and changes in the implied volatility index, while the association is positive for low-interest rate (funding) currencies. That is, investing (funding) currencies tends to depreciate (appreciate) when investor fear increases. A sequential breakpoint test identifies a significant change in this relationship in the period following the 2008 collapse of Lehman Brothers, and another in 2012 following the resolution of the European sovereign debt crisis, which suggests that the relationship is linked to financial system liquidity. During the crisis period, currency returns are much more sensitive to changes in investor fear, and this is particularly so for funding currencies that are perceived to present a safe-haven. The results have important implications for international finance, and those looking to speculate via the carry trade.